Some results about Hypergraph - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
The goal of this paper is to develop a hypergraph point of view for the investigation of properties of candidate keys in the relational datamodel. We give algorithm that find a minimal transversal and all minimal transversal of a given hypergraph. Some another computational problem related to the hyoergraph, the transversal and the minimal transversal and the minimal transversal also are presented.